2001
DOI: 10.1002/1521-3846(200105)21:2<141::aid-abio141>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable -Amylase and Glucoamylase from Thermomyces lanuginosus F1

Abstract: An α-amylase and a glucoamylase produced by Thermomyces lanuginosus F 1 were separated by ionexchange chromatography on Q-Sepharose fast flow. The enzymes were further purified to electrophoretic homogeneity by chromatography on Sephadex G-100 and Phenyl-Sepharose CL-4B. The molecular weights and isoelectric points of the enzymes were 55,000 Da and pH i 4.0 for α-amylase and 70,000 Da and pH i 4.0 for glucoamylase, respectively. The optimum pH and temperatures for the enzymes were found to be 5.0 and 60°C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…such as A. oryzae, Aspergillus ficuum and A. niger were found to give significant yields of α-amylase at pH 5.0 to 6.0 in submerged fermentations (Moller et al, 2004); Knox et al, 2004). Therefore, the pH optimum 5.0 obtained in this work compares well with the works of Ali and AbdelMoneim (1989); Sudo et al (1994) and Odibo and Ulbrich-Hofmann (2001) who reported optimum pH of 5.0 for alpha-amylase from A. flavus var. columnaris, Aspergillus kawachi IFO 4308 and T. lanuginosus respectively which indicated that the organism prefer acidic condition for better enzyme production.…”
Section: Discussionsupporting
confidence: 86%
“…such as A. oryzae, Aspergillus ficuum and A. niger were found to give significant yields of α-amylase at pH 5.0 to 6.0 in submerged fermentations (Moller et al, 2004); Knox et al, 2004). Therefore, the pH optimum 5.0 obtained in this work compares well with the works of Ali and AbdelMoneim (1989); Sudo et al (1994) and Odibo and Ulbrich-Hofmann (2001) who reported optimum pH of 5.0 for alpha-amylase from A. flavus var. columnaris, Aspergillus kawachi IFO 4308 and T. lanuginosus respectively which indicated that the organism prefer acidic condition for better enzyme production.…”
Section: Discussionsupporting
confidence: 86%
“…Some of them are thermostable and very suitable for the industrial applications. T. lanuginosus secretes many enzymes (Fischer et al 1995;Chaudhuri and Maheshwari 1996;Li et al 1997;Bharadwaj and Maheshwari 1999;Singh et al 2000a;Odibo and Ulbrich-Hofmann 2001;Gulati et al 2007;Rezessy-Szabo et al 2007;Khucharoenphaisan and Sinma 2010;Fang et al 2014) that are listed in Table 1. Table 1 suggests that thermophilic microorganisms like T. lanuginosus produces thermostable enzymes that are able to survive at high temperatures as well as extremes of pH conditions (Haki and Rakshit 2003).…”
Section: Thermostable Chitinasementioning
confidence: 99%
“…4, single glucoamylase produced 7.89 mg/ml of glucose, whereas single ␣-amylase produced 1.95 mg/ml of glucose. Since ␣-amylase breaks ␣-1,4-glycosidic bonds in the inner part of starch (liquefaction of starch) [10], ␣-amylase-catalyzed liquefaction mainly produces oligosaccharides with the small amount of glucose as end products [11]. On the other hand, glucoamylase, an exoamylase, cleaves both ␣-1,4-and ␣-1,6-glycosidic bonds [12].…”
Section: Effect Of Single-and Co-enzyme System On the Hydrolysis Of Smentioning
confidence: 99%